2014
DOI: 10.1371/journal.pone.0107518
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Parasites, Habitat Change and Heavy Rainfall Reduce Breeding Success in Darwin's Finches

Abstract: Invasive alien parasites and pathogens are a growing threat to biodiversity worldwide, which can contribute to the extinction of endemic species. On the Galápagos Islands, the invasive parasitic fly Philornis downsi poses a major threat to the endemic avifauna. Here, we investigated the influence of this parasite on the breeding success of two Darwin's finch species, the warbler finch (Certhidea olivacea) and the sympatric small tree finch (Camarhynchus parvulus), on Santa Cruz Island in 2010 and 2012. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 45 publications
3
86
0
Order By: Relevance
“…However, our data also point towards a negative influence of the habitat change (Cimadom et al 2014). On Santa Cruz Island, the Scalesia forest had been reduced to only 1% of its original distribution by previous agricultural activity (Mauchamp and Atkinson 2009), and more recently has been invaded by different introduced plant species (Renteria et al 2012).…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…However, our data also point towards a negative influence of the habitat change (Cimadom et al 2014). On Santa Cruz Island, the Scalesia forest had been reduced to only 1% of its original distribution by previous agricultural activity (Mauchamp and Atkinson 2009), and more recently has been invaded by different introduced plant species (Renteria et al 2012).…”
Section: Introductionsupporting
confidence: 51%
“…In some areas of the Scalesia zone, the Galá-pagos National Park Directorate (GNPD) manually controls R. niveus with machetes and subsequently applies herbicides onto the regrowth to assist in the natural regeneration of the forest. The manual control caused a temporary removal of the understory, and we found that the breeding success of Warbler Finches was significantly lower in areas in which R. niveus had been recently controlled (Cimadom et al 2014). Since arthropods use plants for refuge and/or for food, the removal of the understory may reduce their abundance (Boada 2008).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations